Raloxifene Modulates Microglia and Rescues Visual Deficits and Pathology After Impact Traumatic Brain Injury - Honig, Marcia G.; Del Mar, Nobel A.; Henderson, Desmond L.; O’Neal, Dylan; Doty, John B.; Cox, Rachel; Li, Chunyan; Perry, Aaron M.; Moore, Bob M.; Reiner, Anton (Frontiers in Neuroscience, 2021)
Mild traumatic brain injury (TBI) involves widespread axonal injury and the activation of microglia, which initiates secondary processes that substantially worsen the TBI outcome. The upregulation of cannabinoid type-2 receptors (CB2) when microglia become activated allows CB2-binding drugs to selectively target microglia. CB2 inverse agonists bias activated microglia away from the harmful M1 state toward the helpful M2 state and thus can stem secondary injury cascades. We previously found that treatment with the CB2 inverse agonist SMM-189 after mild TBI in mice produced by focal cranial air blast attenuates the visual deficits and retinal pathology this injury otherwise produces. We have further shown that raloxifene, an FDA-approved estrogen receptor drug used to treat osteoporosis that also possesses CB2 inverse agonism, yields similar benefit in this model through its modulation of microglia. As many different traumatic events produce TBI in humans, it is important that diverse animal models be used to evaluate possible therapies. Here we examine the consequences of TBI created by an impact to the mouse head for visual function and associated pathologies and assess raloxifene benefit. We found that mice subjected to impact TBI exhibited decreases in contrast sensitivity and the B wave of the electroretinogram, increases in light aversion and resting pupil diameter, and optic nerve axon loss, which were rescued by daily injection of raloxifene at 5 or 10 mg/ml for 2 weeks. Raloxifene treatment was associated with a diminution of M1 activation caused by impact TBI, and a decreased M1/M2 ratio in retina, optic nerve, and optic tract. Optic nerves in 10 mg/ml raloxifene impact mice were characterized by large, rounded microglia that appeared to be engulfing damaged axons, suggesting that raloxifene enhances phagocytosis of axonal debris and that this is therapeutic. These results indicate that raloxifene provides benefit for visual system function and pathology following impact TBI. Taken together, our work shows microglial activation drives secondary injury processes after both impact and cranial blast TBI and raloxifene mitigates visual system injury in both cases. The results thus provide a strong basis for phase-2 efficacy testing in human clinical trials.